Unveiling racial biases - Ferreira, Alyssa Lana (Rhodes University, 2026)
This study critically examines transformation efforts in two historically white independent schools in the Eastern Cape, with a particular focus on race. Using cultural capital and critical race theory as analytical frameworks, it evaluates the schools’ approaches to racial issues in relation to the needs and expectations of black alumni, drawing on their lived experiences. The study employs semi-structured individual interviews with former staff members involved in transformation initiatives, black alumni, and external experts in education and transformation. It explores the extent to which private schools’ transformation management surrounding race and transformation efforts align with the realities and expectations of black students, identifying areas of convergence and divergence between institutional policies, their practical application, and student experiences. Findings indicate a persistent gap between the schools’ transformation efforts and the expectations of black alumni between 2013 and 2023. Participants reflect on the challenges of navigating institutions originally designed to exclude them, highlighting the tensions between policy rhetoric and lived reality. This study underscores the necessity of substantive and sustained transformation within educational institutions to address systemic racism. By interrogating the intersection of policy, practice, and student experience, it contributes to ongoing efforts to promote racial equity in South African schools and globally. The findings emphasise the urgency of dismantling systemic barriers and advocating for meaningful, anti-racist change to create inclusive educational environments where all students can thrive.
a critical analysis of transformation efforts in two historically white independent schools in the Eastern Cape
Keywords: Social justice and education (http://id.loc.gov/authorities/subjects/sh2018001376); Discrimination in education (http://id.loc.gov/authorities/subjects/sh85038386); Critical pedagogy (http://id.loc.gov/authorities/subjects/sh91004641); Cultural capital (https://www.wikidata.org/wiki/Q918002)